ANALGESIC AND ANTIINFLAMMATORY EFFECTS OF TOTAL EXTRACT, FLAVONOID FRACTION AND VOLATILE OIL OF SALVIA HYDRANGEA - V.A HAJ HASHEMI; A GHANADI; D MOSAVI (Journal of Research in Medical Sciences, 2000)
Background. Gol-e-arvaneh with the scientific name of salvia hydrangea (Labiatea) belongs to Salvia genus. In traditional medicine it has been used as analgesic, relieving headache, cold remedy, antipyretic and diuretic. Since until now this plant has not been investigated pharacologically. This study was aimed to find any anti-inflammatory or analgesic activity of the plant.
Methods. At first, total extract, flavonoid fraction and volatile oil was prepared. Analgesic effect was assessed using light tail flick and acetic acid writhing test. Male wistar rats (180-220g) and mice (25±2g) were used in these tests. Carrageen in test was used for assessing anti-inflammatory activity.
Results. Total extract and flavonoid fraction could not produce analgesic effect in light tail flick test, while morphine as a standard drug 15 and 30 min. after administration produced 35% and 90% of MPE respectively. In writhing test, total extract and flavonoid fraction had considerable analgesic effect which was comparable to that of indomethacin. Results of Carageenin test showed that both total extract and flavonoid fraction had marked anti-inflammatory activity and volatile oil had only a slight effect.
Discussion. Since potent drugs (such as opioids) show positive response to light tail flick test, it seems that the plant lacks such compounds. Considerable analgesic activity of total extract and flavonoid fraction in writhing test and also their anti-inflammatory activity indicate that this plant is probably useful for relieving pains, particularly with inflammatory origin.